Marriage and Inheritance Laws in the Iranian Legal System - Muhsin; Oyo Sunaryo Mukhlas (al-Afkar, Journal For Islamic Studies, 2024)
The legal system in Iran plays a pivotal role in governing marriage and inheritance, with a particular emphasis on inheritance law. The initial segment of this research provides a comprehensive understanding of inheritance law in Iran. It encompasses an explanation of the fundamental principles underlying the distribution of assets following an individual's demise, as well as the significant influence of Islamic principles within this context. The aim of this research is to offer a thorough insight into the legal framework governing inheritance law in Iran. To achieve this objective, the research employs a literature-based methodology, involving the analysis of legal documents, a review of relevant literature, and an exploration of secondary data sources. The outcomes of this research guide us through critical aspects of inheritance law in Iran, such as how assets are apportioned among heirs in accordance with Islamic principles, changes in inheritance law over time, and significant developments in the interpretation and implementation of these laws. The findings provide profound insights into the role of inheritance law within Iranian society and its complex impact on the individuals and families involved. This understanding is also crucial for the broader social and cultural context in Iran and may serve as a foundation for further consideration of how the law reflects societal values and norms.